ESTIMASI POTENSI NILAI EKONOMI AGROFORESTRI BERBASIS PALUDIKULTUR UNTUK RESTORASI LAHAN GAMBUT - Umami, Mashlahatul; Sari, Eli Nur Nirmala; Haryanto, Rizky Januar (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
Paludiculture-based agroforestry promotes sustainable peatland-use management practices through rewetting activities on drained peatland, revegetating degraded peatland using high-value local tree species and at the same time providing economic benefits for local communities. Due to its potential benefits in maintaining balance between production and protection function of the landscape, paludiculture-based agroforestry in peatlands is purposed to support the restoration efforts. This paper explores the potential, ideal paludiculture-based agroforestry direction, and economic value. We present two scenarios for agroforestry in peatlands: 1) business as usual (BAU) agroforestry by combining native peatland tree species and dryland crops, and 2) paludiculture-based agroforestry by combining native peatland tree species and paludiculture crops. The results show that the economic value of BAU agroforestry ranges from IDR 40.32 million (US2,826) to IDR 133.47 million (US9,355) per hectare per year (ha/year) and paludiculture-based agroforestry from IDR 44.22 million (US3,099) to IDR 106.73 (US7,481) million ha/year. Taking the BAU model as baseline, the paludiculture model leads to higher emission reduction with a value of IDR 6.2 million (US435) to IDR 25.21 million (US1767) per ha/year relative to the BAU. This implies a wider scope of ecological and economic benefits offered by the paludiculture-based agroforestry model compared to the BAU.